Law, custom, and statute in the Muslim world : studies in honor of Aharon Layish - Layish, Aharon, 1933-; Shaham, Ron. (Studies in Islamic law and society,, 2007)
This collective volume, in honor of Aharon Layish, deals with the main components in the laws of Islamic societies, past and present: sharīʿa , custom, and statute. Some chapters focus on one of these components, other discuss the interplay between two or even all three of them. The geographical coverage of the volume is wide, from the Balkans to Yemen, and from Iraq to the Maghrib. The chapters are based on a variety of sources: fiqh literature, fatwās , court decisions, judicial circulars, biographical dictionaries and chronics. The volume will be of special interest to historians, social scientists and lawyers working on Islamic and Israeli laws, and to those interested in gender studies, the Israeli-Palestinian conflict and Islamic cultures at large.